2008
DOI: 10.1016/j.marenvres.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative immunochemical evaluation of fish metallothionein upon exposure to cadmium

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Hepatic MT synthesis is induced by a number of metals, cytokines and stress hormones as well as by a wide range of chemicals, many of which act indirectly via stress or inflammatory response (Coyle et al 2002). MT transcript and protein are induced in fish by a variety of bivalent metals, including Cd, Zn, Cu, Pb and Hg (Ikebuchi et al 1986;Carginale et al 1998;Riggio et al 2003b;Eroglu et al 2005;Alvarado et al 2006;Yudkovski et al 2008). Therefore, MTs have become of great interest for assessing pollution in the marine environment and are seen as potential biomarkers of metal exposure in fish (Georgen and Olssen 1994;Langston et al 2002;Sarkar et al 2006;Nesto et al 2007;Fernandes et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic MT synthesis is induced by a number of metals, cytokines and stress hormones as well as by a wide range of chemicals, many of which act indirectly via stress or inflammatory response (Coyle et al 2002). MT transcript and protein are induced in fish by a variety of bivalent metals, including Cd, Zn, Cu, Pb and Hg (Ikebuchi et al 1986;Carginale et al 1998;Riggio et al 2003b;Eroglu et al 2005;Alvarado et al 2006;Yudkovski et al 2008). Therefore, MTs have become of great interest for assessing pollution in the marine environment and are seen as potential biomarkers of metal exposure in fish (Georgen and Olssen 1994;Langston et al 2002;Sarkar et al 2006;Nesto et al 2007;Fernandes et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Very similar results were presented in other study [28], in which it was shown that most of cadmium (60%) was located in the heat stable cytosolic component, probably bound by metallothioneins, protecting the liver from cadmium toxicity. In this study [29], the authors paid their attention to cadmium distribution in yellow perch ( Perca flavescens ) liver. Perches were under several natural long-term exposure of water-born cadmium.…”
Section: Resultsmentioning
confidence: 99%
“…Yudkovski et al . (2008) also reported that MT transcript induction appeared only upon exposure to relatively high levels of Cd, not generally existing in the coastal environment or in rivers. However, acclimatization to elevated levels of trace elements may be achieved by altered uptake or elimination rates (Dallinger et al ., 1996).…”
Section: Complications In Use Of Thiols As Biomarkersmentioning
confidence: 96%
“…Yudkovski et al . (2008) reported that Cd is accumulated in the liver and its further transportation to other organs is limited. It seems that the chronic exposure which may lead to steady state Cd hepatic levels requires long-term exposure to high Cd levels.…”
Section: Cadmium – Uptake and Toxicokineticsmentioning
confidence: 99%